Experimental and numerical study of cavitating particulate flows in a Venturi tube. (29th June 2020) - Shi, Hongbo; Li, Mingda; Liu, Qingxia; Nikrityuk, Petr
Highlights: Experimental and numerical studies of cavitation phenomena with different solid mass concentrations (Ws = 5–30 wt%). A new four-phase global model was developed and validated against experimental data. The addition of solid particles has significant effects on the generation of cavitation. Abstract: Cavitating Venturi tubes play a significant role in mineral processing and their performance depends to a great extent on the presence of solid particles. This work is devoted to experimental and numerical studies of cavitation phenomena in a Venturi tube with different solid mass concentrations (W s  = 5–30 wt%). Numerical simulation is carried out with an axisymmetric 2D CFD-based model available in the commercial CFD software ANSYS FLUENT 16.2. The simulation is conducted using the Eulerian-Eulerian approach. A new four-phase global model was developed based on a simpler engineering approach and validated against experimental data. Predictions of the pressure drop obtained from the CFD model are generally in good conformance with experimental measurements. Both the numerical and experimental studies reveal that the addition of solid particles in the cavitating Venturi tube has significant effects on the generation of cavitation. The outcomes show that the higher solid mass concentration is of benefit to cavitation intensity. The proposed CFD model has proved to be an efficient and reliable tool in predicting the cavitation activities and performance characteristics of the cavitating Venturi tube.